2012
DOI: 10.1103/physrevc.86.055801
|View full text |Cite
|
Sign up to set email alerts
|

Proton capture on17O and its astrophysical implications

Abstract: Background: The reaction17 O(p, γ) 18 F influences hydrogen-burning nucleosynthesis in several stellar sites, such as red giants, asymptotic giant branch (AGB) stars, massive stars and classical novae. In the relevant temperature range for these environments (T9 = 0.01-0.4), the main contributions to the rate of this reaction are the direct capture process, two low lying narrow resonances (Er = 65.1 and 183 keV) and the low-energy tails of two broad resonances (Er = 557 and 677 keV).Purpose: Previous measureme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(56 citation statements)
references
References 32 publications
(79 reference statements)
5
49
2
Order By: Relevance
“…The following literature data were considered: Hager et al [12] 18 F reaction in the lower part of the studied energy range. Besides the present work, the partial cross sections of Rolfs [5] and Kontos et al [11] are also shown as discussed in the text. The lines through the points are only to guide the eye.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…The following literature data were considered: Hager et al [12] 18 F reaction in the lower part of the studied energy range. Besides the present work, the partial cross sections of Rolfs [5] and Kontos et al [11] are also shown as discussed in the text. The lines through the points are only to guide the eye.…”
Section: Discussionsupporting
confidence: 59%
“…Figure 5 shows the measured cross section in this energy range. In order to compare at least the energy dependence of the cross section, besides the present data, partial cross sections measured by Rolfs [5] and Kontos et al [11] are also included in the figure. As in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After the pioneering work of Rolfs (1973) in the seventies, several studies (Fox et al 2005;Chafa et al 2007;Newton et al 2010;Hager et al 2012;Kontos et al 2012;Scott et al 2012) have determined the reaction rate with improving precision in the past decade. Nevertheless, at the temperatures relevant for AGB nucleosynthesis, the reaction rate is dominated by the lowest energy resonance, E cm = 65 keV, which is too weak to be directly measured with the current experiment possibilities.…”
Section: Reaction Rate Uncertaintiesmentioning
confidence: 99%